Influence of Contrast Media on Bone Mineral Density (BMD) Measurements from Routine Contrast-Enhanced MDCT Datasets using a Phantom-less BMD Measurement Tool - Toelly, Andrea; Bardach, Constanze; Weber, Michael; Gong, Rui; Lai, Yanbo; Wang, Pei; Guo, Yulin; Kirschke, Jan; Baum, Thomas; Gruber, Michael (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Aim To evaluate the differences in phantom-less bone mineral density (BMD) measurements in contrast-enhanced routine MDCT scans at different contrast phases, and to develop an algorithm for calculating a reliable BMD value.Materials and Methods 112 postmenopausal women from the age of 40 to 77 years (mean age: 57.31 years; SD 9.61) who underwent a clinically indicated MDCT scan, consisting of an unenhanced, an arterial, and a venous phase, were included. A retrospective analysis of the BMD values of the Th12 to L4 vertebrae in each phase was performed using a commercially available phantom-less measurement tool.Results The mean BMD value in the unenhanced MDCT scans was 79.76 mg/cm³ (SD 31.20), in the arterial phase it was 85.09 mg/cm³ (SD 31.61), and in the venous phase it was 86.18 mg/cm³ (SD 31.30). A significant difference (p < 0.001) was found between BMD values on unenhanced and contrast-enhanced MDCT scans. There was no significant difference between BMD values in the arterial and venous phases (p = 0.228). The following conversion formulas were calculated using linear regression: unenhanced BMD = -2.287 + 0.964 * [arterial BMD value] and -4.517 + 0.978 * [venous BMD value]. The intrarater agreement of BMD measurements was calculated with an intraclass correlation (ICC) of 0.984 and the interobserver reliability was calculated with an ICC of 0.991.Conclusion Phantom-less BMD measurements in contrast-enhanced MDCT scans result in increased mean BMD values, but, with the formulas applied in our study, a reliable BMD value can be calculated. However, the mean BMD values did not differ significantly between the arterial and venous phases.Key points Citation Format
Keywords: phantom-less; routine CT; contrast agents; calculation formula; bone mineral density